Studi Analisis Potensi Energi Angin Sebagai Pembangkit Listrik Tenaga Angin Di Kawasan Meulaboh - Maidi Saputra; pribadyo pribadyo (universitas teuku umar, 2015)
Which more lower deficit of fossil energy for generated power plant, in order to need to do wind power generation plant analysis based on renewable energy which is wind turbine horizontal type. This study is analyzing a power system with electric power load Meulaboh town by using a hybrid power generation system which HOMER between wind turbines and diesel generators. Wind resources are used is measured by BMKG Meulaboh Station, which is 6 m/s and the value of the price of diesel fuel used by the generator is equal to 0.5 /L. The results of the simulation is given by the value of the Net Present Cost (NPC) and the lowest, in the amount of 66,535,084 for the value of Renewable Factor (RF) was 58% and for the value of Renewable Factor (RF), the largest at 71%, the value of the Net Present Cost (NPC) amounted to 68,091,256. Keywords: Wind Turbine, Homer, Power Plants, Net Present Cost (NPC), Renewable Factor (RF).